PLACEMENT AND TRANSFERENCE IN PSYCHOSIS: : A CASE STUDY (PRÁXIS EM SAÚDE, 2025)
Psychotherapeutic care allows for the analysis and elaboration of processes that cause suffering to the subject. Through placement, it is possible to identify the emergence of a facilitating movement that enables the subject to find relief from their suffering. The aim is to demonstrate the role of placement in the psychotherapy of a patient with a psychotic structure, focusing on the development of the therapeutic bond and autonomy in the therapeutic process, fostering mental health self-care and greater quality of life. Throughout the sessions, it was possible to identify that the patient increased self-care, engaging in other activities beyond psychotherapy, such as physical exercise. Placement was observed to be fundamental to the patient’s autonomy.